2024
DOI: 10.3390/su16031333
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating E-Government Development among Africa Union Member States: An Analysis of the Impact of E-Government on Public Administration and Governance in Ghana

Bernard John Tiika,
Zhiwei Tang,
Jacob Azaare
et al.

Abstract: The adoption of e-government promises efficiency in the delivery of government services to citizens across various sectors of the economy. Due to this, most Global North countries have advanced in the deployment of e-government for improving public-service delivery. Unfortunately, most African countries, including Ghana, are still lagging in e-government development. This study examined e-government development across African Union member states. It explored the role of e-government in the reform of public adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Kassen, Maxat [41] analyzes blockchain developers' perspectives on decentralized service delivery and details the unique algorithms of lifecycle ledgers, arguing that this technology can reliably and securely record e-government transactions. Tiika, Bernard John et al [42] found that the adoption of e-government is expected to improve the efficiency of government service delivery to citizens across economic sectors and will have a transformative impact on public administration and social governance. Unlike existing studies, this paper enriches the research on the impact of e-government development on governments, firms, and individuals by focusing on the specific impact of e-government on the next generation of productive capacity at the micro level.…”
Section: Discussionmentioning
confidence: 99%
“…Kassen, Maxat [41] analyzes blockchain developers' perspectives on decentralized service delivery and details the unique algorithms of lifecycle ledgers, arguing that this technology can reliably and securely record e-government transactions. Tiika, Bernard John et al [42] found that the adoption of e-government is expected to improve the efficiency of government service delivery to citizens across economic sectors and will have a transformative impact on public administration and social governance. Unlike existing studies, this paper enriches the research on the impact of e-government development on governments, firms, and individuals by focusing on the specific impact of e-government on the next generation of productive capacity at the micro level.…”
Section: Discussionmentioning
confidence: 99%
“…Adapting evaluation frameworks for the East African context requires a holistic understanding of regional context, socioeconomic factors, technological infrastructure, governance dynamics, and user perspectives. Incorporating these considerations into evaluation processes, policymakers and stakeholders can assess the effectiveness and impact of e-government initiatives accurately and drive continuous improvement in digital governance practices [16,17].…”
Section: Adaptation Of Framework For the East African Contextmentioning
confidence: 99%